The existence of a Latin American mortality pattern: an analysis of the Colombian an Venezuela cases (1985)
Given the demographic and socio-economic importance of knowing the age mortality pattern of a country, the objective of this project is to determine the validity of the "Latin American'' mortality pattern estimated by the United Nations, taking specifically two countries included in the Latin American group: Colombia and Venezuela, for which the last two intercensal periods are analyzed.